Othello-dor: Racialized Odor In and On Othello - Steingass, Benjamin (Multicultural Shakespeare: Translation, Appropriation and Performance, 2020)
For Shakespearean scholars, the subject of scent in his work has remained relatively lukewarm to discussion. Shakespeare’s use of smell is not only equal to that of his other senses, but smell’s uniquely historical record both on and off the stage illuminate his works in more ways than currently perceived. Shakespeare’s usage of smell is found throughout his works, and their importance on the late Elizabethan and early Jacobean stage present a playwright-director that was exceptionally in-tune with his audiences on the page and in person. Positioned at this culturally significant point in Shakespeare’s career, one work’s utilization of scent textually and theatrically fully explicates the importance of odor in a societal, racial, and domestic capacity: Othello. This article explores and establishes the importance of smell in relation to textual Othello, his “dyed in mummy” handkerchief, and Desdemona in the written tragedy. Additionally, it studies the heighted focus of smell in Othello on a metatheatric level for Shakespeare on his early modern stage, calling attention to the myriad of odors contained in and around his Renaissance theatre and the result effect this awareness would have had on his contemporary audiences in their experience of Othello as a uniquely smell-oriented show.